Targeting myeloid-derived suppressor cells in tumor immunotherapy: Current, future and beyond - Zhao, Yang; Du, Junfeng; Shen, Xiaofei (Frontiers in Immunology, 2023)
Myeloid-derived suppressor cells (MDSCs) are one of the major negative regulators in tumor microenvironment (TME) due to their potent immunosuppressive capacity. MDSCs are the products of myeloid progenitor abnormal differentiation in bone marrow, inhibiting the immune response mediated by T cells, natural killer cells and dendritic cells, promoting the generation of regulatory T cells and tumor-associated macrophages, driving the immune escape and finally leading to tumor progression and metastasis. In this review, we highlight key features of MDSCs biology in TME that are being explored as potential targets for tumor immunotherapy. We discuss the therapies and approaches that aim to reprogram TME from immunosuppressive to immunostimulatory circumstance, preventing MDSC immunosuppression activity, promoting MDSC differentiation, impacting MDSC recruitment and abundance in tumor site. We also summarize current advances in the identification of rational combinatorial strategies to improve clinical efficacy and outcomes of cancer patients, via deeply understanding and pursuing the mechanisms and characterization of MDSCs generation and suppression in TME.